The exchange economy of pre-colonial tropical Africa - Sundström, Lars (London : C. Hurst and company, 1974)
This study review and evaluate the vast historical material on conditions and methods of exchange in West Africa, and on the basis of this evaluation to discuss conclusions and theories concerning trade in pre-colonial Africa colonies.
Reprint of the 1965 ed. published in Uppsala which was issued as no. 24 of Studia ethnographica Upsaliensia under title: The trade of Guinea.
Originally presented as the author's thesis, Uppsala, 1965.
Includes bibliographical references.
II 18/01/2019
Loans
Keywords: Ghana (Region)